Languaging Network Learning: The Emergence of Connectivism in Architectonic Thought - Dennis, Jeremy (International Review of Research in Open and Distributed Learning, 2020)
As technological advancements and online education transform higher education, the achievement gap among students is widening rather than closing. Critics suggest that we need to reassess the promises of online education and the connectivism or network learning that is sometimes employed as its pedagogical underpinning. As scholars and practitioners struggle to define connectivism as a learning theory, many often exclude language as a feature in its conceptualization. This practice is at odds with architectonic thought, the philosophical tradition in which constructivist theories of learning are rooted. This article reveals the central role that language and texts play in architectonic thought and why they are inseparable from our understanding of knowledge and network learning. When we recognize language as a medium and model for reflection and criticality in the architectonic tradition, we are better positioned to use pedagogy and computer technology to transform online education and reorient our competing views of connectivism.